2018
DOI: 10.1111/ases.12676
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of laparoscopic percutaneous extraperitoneal closure for inguinal hernia in infants younger than 6 months: A comparison with conventional open repair

Abstract: Introduction This study aimed to compare the safety and efficacy of laparoscopic percutaneous extraperitoneal closure (LPEC) and conventional open repair (OR) for inguinal hernia in infants younger than 6 months. Methods The medical records of 202 patients who had undergone LPEC or OR at an age younger than 6 months between 2010 and 2016 were reviewed. Patient characteristics and surgical outcomes were compared between LPEC and OR. Results In total, there were 120 LPEC (76 males, 44 females) and 83 OR (76 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
(33 reference statements)
2
14
0
Order By: Relevance
“…In our meta-analysis, we included a retrospective study by Zenitani et al that involved patients aged under 6 months. They reported that compared with OHR, LHRE was better in terms of the MCIH incidence and operation time [41]. Additional trials involving patients under 1 year of age should be conducted to further generalize the results.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In our meta-analysis, we included a retrospective study by Zenitani et al that involved patients aged under 6 months. They reported that compared with OHR, LHRE was better in terms of the MCIH incidence and operation time [41]. Additional trials involving patients under 1 year of age should be conducted to further generalize the results.…”
Section: Discussionmentioning
confidence: 96%
“…A total of 16 studies compared the incidence of metachronous hernia between the LHRE and OHR groups, and 15 of them with a total of 14,416 patients (5207 patients in the LHRE group and 9209 patients in the OHR group) with the diagnosis of unilateral inguinal hernia who received operation were assessed [21,[23][24][25][26][27]29,32,33,36,37,[40][41][42][43]. The pooled result indicated that LHRE resulted in a considerably lower incidence of metachronous hernia compared with OHR (RR: 0.11, 95% CI: 0.07 to 0.17; p < 0.00001; I 2 = 4%; Figure 2).…”
Section: Metachronous Herniamentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, laparoscopic herniorrhaphy is a commonly adopted method of herniorrhaphy in clinical practice, which has the advantages of less trauma, a clear field of vision, high safety and reliability in tissue separation and mesh placement, and remarkable efficacy. However, all surgery leads to trauma and will cause a stress response, inducing varying degrees of damage to the immune function [ 3 , 4 ]. Different anesthetic methods lead to different stress response intensities and immune function damage [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%